Risk factors for stunting in BADUTA in the working area of the Langga Umbung Health Center, South Labuhan Batu District - Sipayung, Ika Manda Yulie; Nababan, Donal; Silitonga, Evawani Martalena (Science Midwifery, 2024)
This study aims to identify the risk factors for stunting among children under two years old (baduta) in the working area of Langga Payung Health Center, South Labuhan Batu Regency. Stunting is a chronic nutritional problem caused by insufficient nutritional intake over a prolonged period, leading to impaired physical and mental growth and development. This research employs a case-control study design with samples of mothers with stunted and non-stunted children. A total of 248 mothers were sampled using purposive sampling techniques. The results indicate that maternal education, maternal knowledge, and family income are significantly associated with stunting incidence. Appropriate interventions targeting these factors are expected to reduce the prevalence of stunting in the area.